Does SGLT2 Inhibition Affect Sympathetic Nerve Activity in Type 2 Diabetes? - Dimova, Rumyana; Tankova, Tsvetalina (Hormone and Metabolic Research, 2020)
SGLT2 inhibitors increase renal glucose excretion and thus decrease both fasting and postprandial plasma glucose levels. The effects of SGLT2 inhibition outweigh those on glycemic control and are also associated with the induction of hemodynamic changes that improve cardiovascular and renal function in people with type 2 diabetes. The exact mechanisms have not yet been completely clarified. This review is focused on the potential relationship between SGLT2 inhibition and sympathetic nerve activity. There is accumulating evidence for a suppressive effect of SGLT2 inhibitors on the sympathetic nerve tone, which might be a putative mechanism for cardiovascular protection in subjects with type 2 diabetes.
Keywords: SGLT2 inhibitor; sympathetic nervous system; type 2 diabetes